Using functional analytic psychotherapy strategies for supporting latinas victims of interpersonal partner violence - Muñoz-Martínez, Amanda M. (2022)
Interpersonal partner violence (IPV) is a worldwide public health problem. As a result of IPV, victims report high rates of physical and behavioral disabilities. Help-seeking behaviors are key to obtaining support on facing and managing IPV. Cultural practices such as machismo, marianismo, and familismo are related to keeping quiet and remaining in an abusive relationship in Latinas. Difficulties in sharing emotions, setting interpersonal boundaries, and communicating needs are also behavioral barriers to seeking help in this population. All these factors are associated with social disconnection which reduces victims’ chances of obtaining support in risky situations. Although several programs have been developed for helping victims of IPV, more evidence on adaptions to particular cultural and interpersonal struggles faced by Latinas’ victims is needed. Functional Analytic Psychotherapy (FAP) proposes that therapeutic relationships based on intimacy can help victims of IPV to identify characteristics of those relationships that provide help when they need it. In this theoretical article, several FAP-based strategies aid therapists working with Latinas’ victims of IPV in strengthening clients’ interpersonal functioning and defeating cultural barriers when seeking help.